Determinants of food banks’ sustainability: the case of Kuala Lumpur / Zubaidah Mohd Ali Tan, Firdaus Ahmad Fauzi and Wan Hayati Wan Bujang - Mohd Ali Tan, Zubaidah; Ahmad Fauzi, Firdaus; Wan Bujang, Wan Hayati (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Food Banks, be it private centres, government agencies, or independent groups, are essential in the effort to enhance food security in Malaysia. In recent economic instability, more and more Malaysian citizens were forced into poverty. Natural disasters and emergencies also sometimes force people to desperately gain access to food supply. Both of these conditions warrant the establishments of food banks in effort to provide aid to these people. Nevertheless, the concept of food bank is quite new in Malaysia, and not many people really aware about the concepts and operations of food banks. Whereas, in European countries, the concepts and operations of food banks is common, and continously improvised to increase its efficiency and effetiveness. Therefore, this research intent to discover the definition of food banks, especially from the perspective of food banks operators themselves. In addition, the researcher hopes to conduct sustainability analysis (by qualitative approach) on the food banks current operations, as well as proposing recommendations to improve aspects of food bank’s practices in the future. Said intentions will be achieved by completing these research objectives; (i) to define the sustainability of Malaysia’s food banks, (ii) to explore the benefits and challenges of Malaysia’s food banks, (iii) to explore future opportunities and recommendations to improve Malaysia’s food banks management and operations, and (iv) to propose a model of Determinants of Malaysia’s Food Bank Sustainability. The derived information will provide a glimpse of the future for food bank initiatives, thus determining its sustainability and its way forward in navigating through today’s numerous issues and challenges.